The Taxonomy Spatial Measure of Development in the Standard of Living Analysis - Kuc, Marta Ewa (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
Incorporation of spatial relationships in the construction of taxonomy measure of development is gaining popularity in Polish literature. However, there is no one common idea concerning how the spatial relationship should be taken into account when creating a synthetic variable nor, indeed, where the spatial weight matrix should be placed. It seems that the inclusion of spatial relationships is more important in smaller regions’ analysis, as they are more affected by the situation in the neighbourhood. This explains why, in this research, rankings of the standard of living in Nordic regions were constructed on the basis of proposals presented by Antczak, Pietrzak and Sobolewski, Migała-Warchoł and Mentel. The aim of this study is to identify the advantages and disadvantages of above-mentioned approaches and to compare the compliance of results obtained from them.